Statistical Assessment of the Impact of Living Standard Indexes of the Population on the Volume of Private Deposits - S. G. Babich; E. S. Darda (Статистика и экономика)
Purpose of the study. One of the most important functions of the Russian banking sector is the accumulation of temporarily free funds of the population for further active operations, including lending to legal entities and individuals. The volume of deposits of individuals is influenced by various factors, the main ones being indexes of the standard of living of the population, which vary significantly in the regions of the country. In the context of significant differences in the spatial development of regions, it is advisable to carry out a statistical analysis of the influence of the main indexes of the standard of living of the population on the volume of funds attracted by credit institutions from the population in the regions of the Russian Federation. The purpose of this study is a statistical analysis of the dynamics and structure of household deposits, as well as an assessment of the impact of the main indexes of the population’s standard of living on the volume of household funds attracted by credit institutions.Research methods and sources of information. The following statistical tools were used: structural and dynamic analysis, cluster analysis, correlation and regression analysis, as well as tabular and graphical methods for presenting research results. The information base is the official statistical data of the Federal State Statistics Service (Rosstat) and the Central Bank of RussiaResearch results. The analysis of the dynamics of the volume of deposits of individuals showed an increase in the volume of private deposits in rubles with a significant reduction in deposits in foreign currency in all federal districts of the country. As a result of studying the regional structure of deposits of individuals in credit institutions, three federal districts can be identified, the share of which is 73,5% in the total volume of private deposits in the country. The use of the cluster analysis method made it possible to identify three groups of regions. The first cluster included three subjects that are characterized by the highest values of the volume of deposits per capita. The second cluster consisted of 66 regions of the country in which the level of development of savings remains low. In 13 subjects included in the third cluster, there is an average level of depositing funds in credit institutions of the country. The use of the method of correlation and regression analysis made it possible to identify the most significant impact on the volume of private deposits per capita of the average per capita monetary income of the population, i.e. a high level of cash income will contribute to an increase in the volume of citizen deposits attracted by credit institutions, as well as a moderate direct impact of the level of employment of the population. In addition, in certain groups of regions, the degree of influence of factor characteristics on the volume of private deposits per capita varies.